(De)legitimation on Twitter: the case of Speech Acts in Buhari-Atiku campaign rhetoric during Nigeria’s 2019 elections - Zubairu Malah,; Shamala Paramasivam,; Hazlina Abdul Halim,; Nor Shahila Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The 2019 Presidential Elections in Nigeria saw unprecedented intensity of campaign on Twitter, particularly between President Buhari and his challenger, Atiku Abubakar, the most dominant candidates of the two major parties, APC and PDP. The intense rhetoric was markedly amplified by Buhari's controversial decisions of suspending the Chief Justice of Nigeria and postponing Presidential and National Assembly Elections. The President tried to justify his decisions, while Atiku challenged them. Therefore, the purpose of this study was to investigate the use of Speech Acts for (de)legitimation in Buhari-Atiku tweets on these incidents. Hence, while adopting Critical Discourse Analysis, the study applied Searle's (1969) Speech Acts, Reyes' (2011) Strategies of Legitimation in Political Discourse and van Dijk's (2006, 2011) Rhetorical Discursive Strategies. The data comprised 53 tweets from the official Twitter handles of Buhari and Atiku. The results indicate that while Buhari relied on Assertives (44%), Atiku relied on Expressives (40%) for (de)legitimation. Further analysis found that Buhari's Assertives were utilised to make claims, explain, and ultimately legitimate his decisions through Appeal to Emotions (55%) or Rationality (37%). But Atiku's Expressives were mainly used to delegitimate Buhari's decisions through Appeal to Emotions (87.5%), blaming the President for dishonest rationale, emphasising the unconstitutionality of the decisions and discrediting all explanations in order to arouse negative emotions. The study concluded that Assertives and Expressives are vital for constructing political (de-)legitimation on Twitter and that the strategy of Appeal to Emotions predominates (de)legitimatory discourse on Twitter.